(untitled) (Historia, 2021)
This article looks into the reception of contemporary dance theatre by South African audiences and critics during the last decade of the twentieth century, with specific reference to the State Theatre Dance Company (STDC), widely recognised as the best in South Africa. the success of the STDC can, to a large extent, be ascribed to European and American input as far as artistic inspiration from the works of international choreographers and the development of local dancers (technique and discipline) are concerned.